Characterizing acceptable and appropriate implementation strategies of a biobehavioral survey among men who have sex with men and others assigned male who have sex with men in Zimbabwe - Lauren E. Parmley; Sophia S. Miller; Tiffany G. Harris; Owen Mugurungi; John H. Rogers; Avi Hakim; Godfrey Musuka; Innocent Chingombe; Munyaradzi Mapingure (Public Library of Science (PLoS), 2022)
Key populations including men who have sex with men (MSM), female sex workers, people who inject drugs, transgender persons, and prisoners account for nearly 50% of new HIV infections globally. To inform the HIV response and monitor trends in HIV prevalence and incidence among key populations, countries have increased efforts to implement biobehavioral surveys (BBS) with these groups as part of routine surveillance. Yet the marginalized nature of populations participating in a BBS requires contextually acceptable and appropriate strategies for effective implementation. We conducted a formative assessment to inform the first BBS conducted with MSM and others assigned male who have sex with men (OAMSM) in Zimbabwe, where same-sex sexual behaviors are illegal and highly stigmatized and describe applications of our findings. Qualitative data were collected through four focus groups with 32 MSM/OAMSM and 25 in-depth interviews (15 MSM/OAMSM, 10 service providers/gatekeepers) from December 2018 to January 2019. Rapid assessment techniques were employed including rapid identification of themes from audio recordings and review of detailed field notes and memos to identify key themes. Findings from this assessment included contextually relevant considerations including behaviors and terminology to avoid when working with MSM/OAMSM in Zimbabwe, appropriate compensation amounts for survey participation, proposed data collection sites, and differences in sexual openness, marital status, and networks among younger and older MSM/OAMSM. Participants also reported strong network ties suggesting respondent-driven sampling-a peer chain referral approach-to be an appropriate recruitment method in this context. Taken together, these findings highlighted key considerations and strategies for implementation to ensure the subsequent BBS in Zimbabwe was both acceptable and appropriate. These results and applications of these results are important for informing surveillance efforts and broader HIV-related engagement efforts among MSM/OAMSM in Zimbabwe as well as in other contextually similar countries in Southern Africa.